2016
DOI: 10.21577/0103-5053.20160262
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Monohydroxylation Products from rac-Camphor by Marine Fungus Botryosphaeria sp. Isolated from Marine Alga Bostrychia radicans

Abstract: This manuscript describes the biooxidation of rac-camphor using whole cells of marine-derived fungus Botryosphaeria sp. CBMAI 1197. The main biotransformation products of this monoterpene were achieved via a hydroxylation reaction and occurred with 5 days of rac-camphor incubation. Products were identified by means of gas chromatography mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) data. The major hydroxylated products were 6-endo-hydroxycamphor, 6-exo-hydroxycamphor, 5-exo-hydroxycamphor, 5-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…(B) Hydroxylation of rac -camphor by Botryosphaeria sp. CBMAI 1197 (De Jesus et al, 2017). (C) Biotransformation of (–)-Ambrox and (–)-Sclareol by marine-derived fungi (Martins et al, 2015).…”
Section: Whole-cell Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Hydroxylation of rac -camphor by Botryosphaeria sp. CBMAI 1197 (De Jesus et al, 2017). (C) Biotransformation of (–)-Ambrox and (–)-Sclareol by marine-derived fungi (Martins et al, 2015).…”
Section: Whole-cell Processesmentioning
confidence: 99%
“…The major product was 6- endo -hydroxycamphor, but the biotransformation process resulted in different monohydroxylated compounds. It is important to note that these modifications in sp 3 carbons are difficult to be performed by conventional methods (De Jesus et al, 2017).…”
Section: Whole-cell Processesmentioning
confidence: 99%
“…These antifouling extracts displayed potent activity against diatoms, microbes, and algal spore settlement. A survey of the literature revealed that the genus Bostrychia is a rich source of several polar substances such as amino acids, brominated sulphated phenols, and terpenoids [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. As might be concluded, the antifouling activity of the polar extract of B. tenella could be partly attributed to the presence of polar function groups including amino, hydroxyl, carbonyl, carboxyl, carbon-carbon double bond, carbon-halogen, and hydrogen-bonding functionalities ( Figure S4 ) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…indicating that this genus is an algal endophyte. The order Botryosphaeriales was found in the marine environment and was isolated as an endophyte of the red algae Bostrychia radicans ( De Jesus et al, 2017 ). Therefore, these three orders could represent the core microbiome of macroalgae.…”
Section: Discussionmentioning
confidence: 99%